Researching hate as an activist: exploring LGBTQ+ online hate, its impacts, and our responsibility towards equality - Keighley, Rachel (Palgrave hate studies, 2024)
"This book examines research as activism through a case study of online hate targeting LGBTQ+ young people. It focuses on key issues concerning defining online hate, LGBTQ+ young people’s experiences of and the harms of online hate. The book introduces the reader to research as activism, exploring how academic research has an obligation to be accountable to the communities we serve. It presents a reconsideration of researching hate that prioritizes the knowledge and expertise of community members above the academic researcher. Drawing on empirical data, the book is a call to action which argues for a moral and personal duty to address social injustices using our privilege as academics. Research as activism requires you to go beyond the four walls of your university to actively respond to socio-political injustices. Thus, the book discusses how researchers can use their academic tools for change. It speaks to academics, students, and practitioners interested in LGBTQ+ identities, hate studies, online safety, and research as activism." --